2020
DOI: 10.1029/2019gh000216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacteria on Aerosols From Dust Events in Dakar, Senegal, West Africa

Abstract: We identify bacteria types on collected dust samples in Dakar Senegal, a region that experiences frequent Saharan dust events. We use classical techniques to identify bacteria types from dust samples. Seventy-seven bacteria types are identified from samples collected by spatula and the QuickTake® 30 air sampling pump. The dominant groups in the first batch of 51 bacteria (collected via deposition) are Micrococcus (33.33%), Bacillus (13.73%), Kytococcus (11.76%), Pseudomonas (9.80%), and Burkholderia (7.84%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Further, Marone et al. ( 2020 ) show that bacteria exists on the surface of dust particles, with some serving as pathogens that could have health impacts in West Africa during the winter and spring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Marone et al. ( 2020 ) show that bacteria exists on the surface of dust particles, with some serving as pathogens that could have health impacts in West Africa during the winter and spring.…”
Section: Introductionmentioning
confidence: 99%
“…Toure et al (2019) showed that there are many asthma cases and acute respiratory infections in Senegal throughout the year. Further, Marone et al (2020) show that bacteria exists on the surface of dust particles, with some serving as pathogens that could have health impacts in West Africa during the winter and spring.…”
mentioning
confidence: 99%
“…All studies were published between 2004 and 2021 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The affected regions that were studied were Asia (32/51, 62.7%), followed by Europe (9/51, 17.6%), America (6/51, 11.8%), Africa (4/51, 7.8%) and Australia (1/51, 2.0%).…”
Section: Resultsmentioning
confidence: 99%
“…and Coxiela burnetti , as well as Coccidioides spp. fungus and influenza A virus [ 10 , 16 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The remaining studies reported opportunistic pathogens, mostly Bacillus spp., Aspergillus spp., etc.…”
Section: Resultsmentioning
confidence: 99%
“…At the Cape Verde islands, besides the ocean, mineral dust is an important aerosol particle source (Fomba et al, 2014). TEP are generally attributed to be ocean-derived compounds however, dust has often been reported to transport attached biological particles (Maki et al, 2019;Marone et al, 2020). During the MarParCloud campaign, dust influences were low to moderate and the aerosol particle mass was found to be predominantly of marine origin (Fomba et al, 2014;.…”
Section: Insert Figurementioning
confidence: 99%